DEVELOPMENT STRATEGY NORTH TORAJA’S HIDDEN GEM IN LEMBANG NONONGAN - Liliana Dewi; Adli Rizky Muharam (International Journal of Social Science, 2022)
Indonesia's Government, through Tourism Ministry, tried hard to recover Indonesia's tourism in the Covid-19 pandemic. One of the strategies is to develop rural tourism in Indonesia. As part of Toraja, South Sulawesi province, Lembang Nonongan village is an embryo of rural tourism categories that can create. This research aims to know Lembang Nonongan village potencies to develop as a tourism destination, how local government and local communities develop Lembang Nonongan village tourism and the obstacles. Qualitative method is this research approach with literature study, documentation and interview to Local Government, Lembang Nonongan village tourism Leader, Leader of Sadar Wisata Lembang Nonongan, and Leader of Lembang Nonongan's public figure and SWOT analysis. The result Lembang Nonongan has natural and cultural potency to develop, the local Government and communities cooperate to enhance, and the obstacles needed to train and educate about tourism, marketing management, and tourism package.